Peran Nilai Pelayanan Kualitas Produk IndiHome terhadap Kepuasan Pelanggan - Minda Agustina; Azhari Akmal Tarigan (Pusat Riset dan Inovasi Nasional, 2023)
This research examines the crucial role of service value and product quality of IndiHome services in influencing customer satisfaction at PT. Telkom Indonesia Tbk, Kandatel Kabanjahe. PT. Telkom Indonesia Tbk, as a State-Owned Enterprise (BUMN), plays a strategic role in the information and communication technology industry in Indonesia. The company's primary focus is to advance society through a range of products and services, with IndiHome as one of its flagship offerings. This study employs a qualitative approach, gathering data through interviews, field observations, and document analysis. The findings indicate that the quality of internet connection, myIndiHome application, and customer loyalty program significantly impact customer satisfaction. A fast and stable internet connection provides users with a better experience. The myIndiHome application facilitates easy access and management of services for customers. Meanwhile, the customer loyalty program successfully retains subscriptions. This research concludes that customer satisfaction is not just an end goal, but also the foundation for building strong and mutually beneficial long-term relationships.